The Role of Linguistics in the Formation of IT-Based Arab Language Learning Methods - Marsiah; Hamidah; Nurul Wahdah; Noor Hujjatusnaini; Muhammad Taufiq (UIN Syekh Wasil Kediri, Indonesia, 2025)
This research examines the role of linguistic science in creating more effective and contextually relevant Arabic language learning methods, particularly through the incorporation of digital technology. Employing a qualitative approach that is both descriptive and analytical, this study investigates the contributions of five key branches of linguistics: phonology, morphology, syntax, semantics, and pragmatics, in developing learning strategies that are not only theoretical but also practical and supportive of communication skill enhancement. It highlights the shortcomings of traditional methods, such as the grammar-translation approach, which often prove to be monotonous and inadequate in training students' communicative abilities. In response, various linguistically-informed learning method and strategies have been devised, including contextual learning, authentic text analysis, project-based learning, and the utilization of interactive technology. The findings indicate that merging linguistic theory with digital media—such as learning applications, speech recognition, and gamification—can boost motivation, improve pronunciation, and deepen understanding of the structure and meaning of the Arabic language. This research aims to inspire the development of innovative Arabic language learning methods that align with modern demands and meet the needs of learners in Indonesia.